2020
DOI: 10.3389/fonc.2020.01102
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 and mutp53 Engage a Positive Feedback Loop Involving HSP90 and the Mevalonate Pathway

Abstract: Oncosuppressor TP53 and oncogene STAT3 have been shown to engage an interplay in which they negatively influence each other. Conversely, mutant (mut) p53 may sustain STAT3 phosphorylation by displacing SH2 phosphatase while whether STAT3 could influence mutp53 has not been clarified yet. In this study we found that pharmacologic or genetic inhibition of STAT3 in both glioblastoma and pancreatic cancer cells, carrying mutp53 protein, reduced mutp53 expression level by down-regulating chaperone HSP90 as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…Mutp53 is recruited to the promoters of several mevalonate pathway genes to induce their expression through its interaction with the master transcription factor SREBP1/SREBP2 (27). In addition, the mevalonate pathway-DNAJA1 axis as well as the STAT3-mevalonate pathway axis are both found to prevent mutp53 from being degraded by CHIP ubiquitin ligase, forming a positive-feedback loop to ensure rapid lipid synthesis (28,29). Mutp53 proteins were also reported to promote nucleotide synthesis through its interaction with ETS2 to activate numerous nucleotide metabolism genes (RRM2, dCK, TK1, GMPS, IMPDH1, PAICS) involved in both the de novo and the salvage pathways required for nucleotide synthesis, leading to elevated nucleotide pools and the subsequent enhancement of GTP dependent protein (GTPase) activity (30,31).…”
Section: Modulating Metabolismmentioning
confidence: 99%
“…Mutp53 is recruited to the promoters of several mevalonate pathway genes to induce their expression through its interaction with the master transcription factor SREBP1/SREBP2 (27). In addition, the mevalonate pathway-DNAJA1 axis as well as the STAT3-mevalonate pathway axis are both found to prevent mutp53 from being degraded by CHIP ubiquitin ligase, forming a positive-feedback loop to ensure rapid lipid synthesis (28,29). Mutp53 proteins were also reported to promote nucleotide synthesis through its interaction with ETS2 to activate numerous nucleotide metabolism genes (RRM2, dCK, TK1, GMPS, IMPDH1, PAICS) involved in both the de novo and the salvage pathways required for nucleotide synthesis, leading to elevated nucleotide pools and the subsequent enhancement of GTP dependent protein (GTPase) activity (30,31).…”
Section: Modulating Metabolismmentioning
confidence: 99%
“…Several ongoing clinical studies are evaluating the effect of niclosamide on cancer treatment [ 159 ]. STAT3 and mtp53 have recently been shown to elicit positive feedback regulation involving HSP90 and the mevalonate pathway [ 160 ]. The HSP chaperone system plays a role in mtp53 stabilization by protecting mtp53 from degradation by E3 ubiquitin ligases [ 28 ].…”
Section: Pharmacological Strategies To Target Both P53 and Stat3 Amentioning
confidence: 99%
“…Other than drugs with identified clinical trials for cancer therapy listed in Table 2 , there are other notable compounds that have been reported to have potential dual effects on STAT3 and p53. One example is AG490, a JAK2/STAT3 inhibitor, which could support the p53–p21 axis to induce Kaposi’s sarcoma-associated herpesvirus (KSHV) lytic cycle activation in lymphoma cells or downregulate HSP90 as well as mtp53 expression in glioblastoma and pancreatic cancer cells [ 160 , 162 ]. Another example is nitazoxanide, an FDA-approved antiprotozoal agent which was proved to have dual inhibitory effects on IL-6/JAK2/STAT3 and p53-dependent signaling pathways in colorectal cancer (CRC) cells [ 163 ].…”
Section: Pharmacological Strategies To Target Both P53 and Stat3 Amentioning
confidence: 99%
“…STAT3 is a very promising target in anticancer therapy, as its inhibition interrupts the release of cytokines that re-activate STAT3 in immune myeloid cells, inducing immune dysfunction, or in B cells, contributing to EBV-driven immortalization, or in established cancer cells, sustaining cell survival [57][58][59][60]. While it has been reported that STAT3 and wtp53 negatively regulate each other [61,62], recent studies have highlighted that STAT3 engages a cross talk with mutp53 in which they sustain each other [24,63,64]. Reducing the release of pro-inflammatory cytokines or using monoclonal antibodies able to neutralize their activity could interrupt the harmful alliance between mutp53 and STAT3, in which these cytokines may act as a bridge.…”
Section: Cross Talk Between Stat3 Upr Autophagy and Mutp53mentioning
confidence: 99%
“…2). As mutp53 is often misfolded, its hyperstability may also depend on the presence of chaperoning molecules such as HSP90 [20,21] whose expression can be regulated by pathways such as PI3K/AKT/mTOR [22] and STAT3 [23,24] (Fig. 3).…”
Section: Introductionmentioning
confidence: 99%